The states that hide in the shadows: the potential role of conical intersections in the ground state unimolecular decay of a Criegee intermediate. Issue 1 (14th December 2021) - Marchetti, Barbara; Esposito, Vincent J.; Bush, Rachel E.; Karsili, Tolga N. V.
Abstract : The ground state unimolecular decay of Criegee intermediates may potentially be influenced by conical intersections. Abstract : Criegee intermediates are of great significance to Earth's troposphere – implicated in altering the tropospheric oxidation cycle and in forming low volatility products that typically condense to form secondary organic aerosols (SOAs). As such, their chemistry has attracted vast attention in recent years. In particular, the unimolecular decay of thermal and vibrationally-excited Criegee intermediates has been the focus of several experimental and computational studies, and it is now recognized that Criegee intermediates undergo unimolecular decay to form OH radicals. In this contribution we reveal insight into the chemistry of Criegee intermediates by highlighting the hitherto neglected multi-state contribution to the ground state unimolecular decay dynamics of the Criegee intermediate products. The two key intermediates of present focus are dioxirane and vinylhydroperoxide – known to be active intermediates that mediate the unimolecular decay of CH2 OO and CH3 CHOO, respectively. In both cases the unimolecular decay path encounters conical intersections, which may play a pivotal role in the ensuing dynamics. This hitherto unrecognized phenomenon may be vital in the way in which the reactivity of Criegee intermediates are modelled and is likely to affect the ensuing dynamics associated with the unimolecular decay of a given Criegee intermediate.